Expression of Concern (Journal of Accounting Research, 2015)
Abstract Robert Libby and Kristina Rennekamp, “Self‐serving attribution bias, overconfidence, and the issuance of management forecasts,” Journal of Accounting Research, vol. 50, no. 1 (March 2012). Section 4 of the above‐referenced paper includes empirical analysis based on survey data obtained from Dr. James E. Hunton. Because of concerns raised by the Bentley Report (available at https://www.bentley.edu/files/Hunton%20report%20July21.pdf ) about the inability to independently verify data that form the basis for certain of Dr. Hunton's published works, the editors of JAR and the authors of the above‐referenced article hereby issue an Expression of Concern with respect to this article. 1 Specifically, the authors have concluded that the validity of the survey data that underlie Section 4 of this article cannot be confirmed, and suggest that the inferences readers draw from the article be adjusted accordingly. 2